Reworked mammal assemblage from the late Miocene of La Pampa Province, Argentina - Montalvo, Claudia Inés (2021)
Fossil-bearing levels of the Cerro Azul Formation, cropping out at Cerro La Bota (central La Pampa Province), are interpreted as amalgamated conglomeradic-sandy bodies, which suggest the episodic development of perennial streams without flow division on a loessic substrate. The mammal assemblage corresponds to the Chasicoan Stage/Age (late Miocene). Micromammal remains result from the leftover prey accumulated by predators in a den site, while macromammals result from an attritional accumulation of individuals inhabiting the area. Bones were buried in a loessic context and different pedogenetic processes acted on them. During the development of episodic streams, remains were reworked and incorporated into the fluvial channel. Reworking explains particularities of the assemblage: 1) size and shape of fossils suggest they were transported together with sedimentary particles after their primary burial; 2) a high percentage of remains with abrasion marks indicates that they were already fossilized when fluvial action modified them; 3) a high number of undetermined fragments with predominance of smooth transverse fractures; 4) predominance of elements with intermediate susceptibility to be transported, and a very high index of isolated teeth/vertebrae; and 5) relative abundance values reflecting an important loss of different skeletal elements. Even though the different primary accumulation could influence these results, we infer that mobilization and breakage generated during the fluvial reworking greatly affected the final anatomical representation. This study allows assigning the assemblage to the channel-lag taphonomic mode, and reinforces the importance of identifying reworking processes to achieve the complete taphonomic history and accurate biochronologic and biostratigraphic interpretations.